Assessment of patient knowledge and awareness of the occurrence of addiction - Książek, Katarzyna; Słowińska, Agata; Kozyra, Katarzyna; Grabska-Kusiak, Kinga; Ścirka, Natalia; Mojsym-Korybska, Sylwia; Jurek, Anna Małgorzata (Journal of Education, Health and Sport, 2018)
Introduction. Drug treatment and substance abuse treatment centers are mostly involved in the treatment of alcohol or drug addicts. At present, an increasing number of patients depend on several psychoactive substances simultaneously. These people have a phenomenon called mixed addiction. Aim. The aim of the study was an attempt to answer the question about the state of mind of psychiatric hospital patients about the occurrence of addiction. Material and methods. The study included a group of 100 patients in the Neuropsychiatric Hospital's Neuropsychiatric Ward and the SPZOZ Psychiatric Day Ward in Kraśnik. The survey was conducted between February and August 2017. The author's questionnaire method was fully anonymous. Results. Misuse of psychoactive substances is a serious social problem. The phenomenon of addiction is more common among men living in rural areas, working professionally in the age range of 31 to 40 years. The respondents acknowledge that their knowledge of narcotics is based on their experience and their friends. Conclusion. Respondents are aware of the occurrence of mixed dependency.